2007
DOI: 10.1021/jp075628b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intermolecular Interactions on the Mössbauer Quadrupole Splitting of Organotin(IV) Compounds as Studied by DFT Calculations

Abstract: The influence of intermolecular interactions on the Mössbauer quadrupole splitting (Delta) of 119Sn was investigated in detail by density functional theory (DFT) calculations. Six organotin(IV) complexes [Me2Sn(acac)2 (1), Ph3SnCl (2), Me3Sn-succinimide (3), Me3Sn-phthalimide (4), Me3SnCl (5), and cHex3SnCl (6)] of known solid-state structures and quadrupole splittings were selected. Theoretical Delta values were calculated for both fully optimized geometries and experimental solid-state structures of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…To gain a clearer understanding of the ME parameters discussed above, a detailed temperature‐dependent study was undertaken of triphenyltin chloride ( 4a ), even though the results of numerous ME analyses have previously been reported in the literature, including those of Gol'danskii et al,3 Shpinel et al,4 Herber et al,5 Stoeckler and Sano,6 Silvestri,7 Karpati et al,8 and Herber 9. The sample of 4 , as received from the MIT group, contained a small amount of an impurity, identified by its ME parameters as probably SnO 2 , although the presence of Ph 3 SnOSnPh 3 could not be excluded.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…To gain a clearer understanding of the ME parameters discussed above, a detailed temperature‐dependent study was undertaken of triphenyltin chloride ( 4a ), even though the results of numerous ME analyses have previously been reported in the literature, including those of Gol'danskii et al,3 Shpinel et al,4 Herber et al,5 Stoeckler and Sano,6 Silvestri,7 Karpati et al,8 and Herber 9. The sample of 4 , as received from the MIT group, contained a small amount of an impurity, identified by its ME parameters as probably SnO 2 , although the presence of Ph 3 SnOSnPh 3 could not be excluded.…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, numerous 119 Sn Mössbauer effect studies of 4 have been reported, including the early studies by Gol'danskii et al,3 Shpinel et al,4 involved in the controversy relating to the existence of the Gol'danskii–Karayagin effect, the 1965 data of Herber et al,5 that of Stoeckler and Sano6 showing a negligible GKE effect up to 180 K, the detailed data of Greenwood and co‐workers13 showing that e 2 qQ (where Q is the nuclear quadrupole moment and q is the electric field gradient) is negative for this compound, further work by Silvestri,7 and a recent study by Karpati et al8 In this study, a detailed examination of 4a over the temperature range 95 < T < 258 K was effected to characterize this material over as wide a range as possible. The ME hyperfine parameters are summarized in Table 1, and are in reasonable agreement with values reported earlier in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…All calculations were done with the software Gaussian G03W D01, using a fine integration grid, tight energy minimization and verified for the absence of imaginary frequencies. The B3LYP method was chosen because it gives good accuracy for single molecule geometries and reasonably accurate IR frequencies for a wide variety of molecular systems [29] as well as for Sn(IV) compounds [30][31][32]. Geometries were compared only for the three complexes for which X-ray data was available.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…It is indicated that these types of functionals can provide better results compared to local spin density approximation or generalized gradient approximations in thermo-chemistry or structural calculations [12]. Density functional theory and hybrid methods are successfully applied in organotin chemistry covering studies such as chemical reactivity description [13], calculating nonlinear optical properties [14][15][16], obtaining 119 Sn isotropic shielding and coupling constants [17][18][19], investigating Mössbauer quadrupole splitting behaviors [20,21], and other structure interpretation studies [22][23][24]. However, organotin(IV) complexes derived from Schiff bases are of interest due to their various important biological properties [25][26][27], synthetic chemistry applications [28,29], and nonlinear optical properties [14][15][16][17], yet theoretical studies concerning complexes derived from ONO-donor type Schiff base ligands are very limited in the literature.…”
Section: Introductionmentioning
confidence: 99%